2018
DOI: 10.3390/socsci7020017
|View full text |Cite
|
Sign up to set email alerts
|

The Boys Club: Engineering a More Positive Environment for Women in Male-Dominated Majors

Abstract: Sexual harassment has been widely studied in the workforce, but the factors that contribute to hostile educational environments for women have received less attention. The present study focuses on male dominance, gender harassment, gender threats, masculinity, and their influences on creating a hostile environment for women in academia. One hundred and forty-two male participants from a private university in the Southwestern United States self-reported their masculinity, completed a group task with a female co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…These findings are similar to what has been found in previous studies, though mostly in a Western context. Worldwide studies have reported the continued existence of a hostile and discriminatory work environment for women (Dresden et al, 2018, Kuchynka et al, 2018, that has impacted negatively on their leadership aspirations (Pacilli et al, 2019, Wolfers, 2017.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are similar to what has been found in previous studies, though mostly in a Western context. Worldwide studies have reported the continued existence of a hostile and discriminatory work environment for women (Dresden et al, 2018, Kuchynka et al, 2018, that has impacted negatively on their leadership aspirations (Pacilli et al, 2019, Wolfers, 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the questions were also related to exploring their perceptions about Vision 2030, and how its promulgation may be impacting their experiences as women leaders, both directly through the policy environment and indirectly through bringing about a transformation in their socio-cultural and family context. Further, there is substantial research that has found impacts of workplace environment and culture on women employees' career development (Dresden et al, 2018, Cross and Linehan, 2006, Kuchynka et al, 2018, and these were also included in the questionnaire. Since the interview questionnaire was developed eclectically, and not based on any standard scale, its validity was established by conducting a pilot study, which included two respondents.…”
Section: Perceptions About Family and Workmentioning
confidence: 99%
“…G. Stephan et al, 2002). Furthermore, highly identified men are more likely to sexually harass women, display more aggressive behaviors, and hold more negative perceptions of female leaders when threatened (Dall’Ara & Maass, 1999; Dresden et al, 2018; Maass et al, 2003; Wade & Brittan-Powell, 2001), suggesting a relationship between masculine identity, threat, and negative attitudes or behaviors towards women.…”
Section: For Whom Is Resistance Strongest? Ingroup Identity As a Mode...mentioning
confidence: 99%
“…women students and faculty, including recruitment and retention (Blackburn, 2017). These studies explore everything from student motivation (Graziano et al, 2012;Smith et al, 2012;Chumbley et al, 2015;Talley and Ortiz, 2017;Leaper and Starr, 2018), self-concept (Sax et al, 2015;Koul et al, 2016;Morton and Parsons, 2018), self-efficacy (Dugan et al, 2013;Verdín and Godwin, 2018), and identity (Robnett et al, 2015;Beals, 2016) to biases (Handley et al, 2015;LaCosse et al, 2016;Moss-Racusin et al, 2018), stereotypes (Cheryan et al, 2015;Barth et al, 2017;Banchefsky and Park, 2018), campus culture (Crenshaw et al, 2017;Dresden et al, 2018), and lived experiences (Maltese and Tai, 2011;Alexander and Hermann, 2016;Smith and Gayles, 2018). Studies covering women faculty members include barriers to tenure (Soto, 2014;Williams and Ceci, 2015;Skewes et al, 2017), promotion (Gumpertz et al, 2017), worklife balance (O'Brien and Hebl, 2008;Adamo, 2013;Pedersen and Minnotte, 2017), and administrative advancement (Avallone et al, 2013;Lopez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%